PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA GRAHA KAORI GROUP DI GIANYAR - I Gede Agus Ari Eka Budi Pratama; I Wayan Surtha; I Gede Aryana Mahayasa (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The purpose of this study was to determine the effect of transformational leadership style and organizational commitment on employee performance and through mediating organizational commitment in the aromatherapy incense product unit in the Graha Kaori Group in Gianyar. The population in this study all employees in Graha Kaori Group were 33 people, the method of determining the sample using a saturated sample. Data is taken by observation, interview, literature study and questionnaire. Data analysis using path analysis and Sobel test. The results showed that the transformational leadership style had a positive and significant effect on employee performance, the transformational leadership style had a positive and significant effect on organizational commitment, the organizational commitment had a positive and significant effect on employee performance with organizational commitment to mediate the relationship between transformational leadership style and employee performance. Limitations of this study only carried out in small populations for further research can be done in larger populations and with the addition of other variables that affect employee performance.